Miley, CNN and The Onion: When fake news becomes realer than real. (2nd January 2016) - Berkowitz, Dan; Schwartz, David Asa
Abstract : Following a twerk-heavy performance by Miley Cyrus on the Video Music Awards program, CNN featured the story on the top of its website. The Onion —a fake-news organization—then ran a satirical column purporting to be by CNN's Web editor explaining this decision. Through textual analysis, this paper demonstrates how a Fifth Estate comprised of bloggers, columnists and fake-news organizations worked to relocate mainstream journalism back to within its professional boundaries.